ANALISIS KETERAMPILAN PROSES SAINS FISIKA MAHASISWA MATERI ALAT-ALAT OPTIK - Yolanda, Yaspin (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2022)
The low science process skills of students taking optical-tools courses are caused because 65 percent of students do not understand the technical instructions for using optical instruments, students' low skills in applying concepts, skills in drawing conclusions, skills in solving hypotheses, skills in interpreting data into the experimental table is still very low, because during lectures they are only glued to learning in class. Furthermore, students only learn theory without doing practical activities regarding the material being studied, so students are not directed to apply aspects of science process skills. Based on the problems above, this study aims to determine (1) the availability of students' physics science process skills on optical instruments, and (2). The solution given in solving the problem of students' physics science process skills. The research was conducted from January to d. May 2021. The subject is physics education student STKIP PGRI Lubuklinggau. The data collection process includes a diagnostic test of the Science Process Skills (KPS) aspect, observation through student worksheets during practicum and interviews. The results of the study are the results of the study are the availability of students' physics science process skills on optical instruments material, namely 82% observation, 85% classification, 87% interpretation, 84% prediction, asking 90% questions, hypothesizing 80%, planning experiments 95%, using 90% of tools and materials, 85% of concepts applied and 87% of communication. Furthermore, the solution to solve the problem of availability of aspects of physics science process skills for students of physics education for optical instruments at STKIP PGRI Lubuklinggau is to train and be trained with students' physics process skills approach so that the availability of aspects of students' science process skills can emerge.Â